EFFECTIVENESS OF IMPLEMENTING THE RANKING 1 GAME LEARNING MODEL ON SCIENCE LEARNING OUTCOMES - Ida Nurul Indah; Lili Dianah; Eldi Mulyana (Journal Civics And Social Studies, 2023)
This research is motivated by the learning outcomes of students who are still below the minimum completeness criteria (KKM) in social studies subjects. this happens because in the social studies learning process the teacher still does not use a variety of learning models, one effort to minimize problems in the learning process is to apply a learning model, this research is one of the learning models that is expected to improve student learning outcomes, namely by using the ranking game learning model 1. the purpose of this research is to improve social studies learning outcomes at SMPN 3 Garut. This type of research is a type of research using a quantitative approach with quasi-experimental methods using pretest and group design control processes. The population in this study were all class VIII SMPN 3 Garut by taking 2 classes as a sample, VIII I 34 students as the experimental class and class VIII D as the class.The instrument in this research is in the form of test questions. The results of this research show that the experimental class experienced a significant increase in learning outcomes after implementing the ranking 1 game learning model. From the results of the presentation analysis of the increase in the experimental class with the moderate category 67.6%, where from the gaint test results it was found that the average significance value was 0.350 which means it was categorized as medium, so it can be concluded that the effectiveness of learning games ranked 1 on social studies learning outcomes has increased and is effective in social studies learning.